Public art in urban space as a tool for spatial justice: Building inclusive cities through the public art project “Ziarah Utara” - Winarno Winarno; Irene Sondang Fitrinitia; Husnul Fitri (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
Rapid urban growth and a development paradigm centered on economic expansion have turned urban space into an arena of competing interests among the state, capital, and citizens. In the context of Jakarta, the northern coastal area has become one of the most vulnerable spaces, experiencing social exclusion, ecological degradation, and the erasure of collective memory due to large-scale development projects. This paper examines how public art can function as a medium for articulating urban issues, producing alternative knowledge, and serving as a practice of urban spatial advocacy. By focusing on the public art project Ziarah Utara by Irwan Ahmett and Tita Salina, this research employs a participatory qualitative approach using a case study method in Kampung Dadap, a coastal area threatened by reclamation. Research-based public art practices such as Ziarah Utara hold significant potential to expand the discourse of urban planning toward a more inclusive, democratic, and spatially just city. More specifically, the process of producing and screening The Last Fisherwoman, culminating in a fundraising campaign to construct a community toilet facility, functioned as an instrument of spatial justice through the production of knowledge, community empowerment, spatial advocacy, and the mobilization of collective action.